2023
DOI: 10.1021/acsnano.3c00535
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Anti-Inflammatory Therapy Aided by Curcumin-Laden Double-Headed Nanoparticles Combined with Injectable Long-Acting Insulin in a Rodent Model of Diabetes Eye Disease

Abstract: Therapeutic interventions that counter emerging targets in diabetes eye diseases are lacking. We hypothesize that a combination therapy targeting inflammation and hyperglycemia can prevent diabetic eye diseases. Here, we report a multipronged approach to prevent diabetic cataracts and retinopathy by combining orally bioavailable curcumin-laden double-headed (two molecules of gambogic acid conjugated to terminal carboxyl groups of poly(D,L-lactide-co-glycolide)) nanoparticles and injectable basal insulin. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…In this study, glucagon levels were significantly lower in the diabetes groups compared to the healthy control group, indicating that glucagon secretion decreased in STZ-induced rats. In previous studies conducted by our lab, a similar trend was observed, wherein glucagon positive cells were significantly lower than the control groups . Following the treatment, glucagon levels increased significantly in the P2Ns-4C-GA and P2Ns groups, and levels were comparable to that of the control group, followed by glucagon levels in the P2Ns-2C-GA and LA INS groups.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In this study, glucagon levels were significantly lower in the diabetes groups compared to the healthy control group, indicating that glucagon secretion decreased in STZ-induced rats. In previous studies conducted by our lab, a similar trend was observed, wherein glucagon positive cells were significantly lower than the control groups . Following the treatment, glucagon levels increased significantly in the P2Ns-4C-GA and P2Ns groups, and levels were comparable to that of the control group, followed by glucagon levels in the P2Ns-2C-GA and LA INS groups.…”
Section: Resultssupporting
confidence: 85%
“…Plasma ALP levels were significantly lower in the P2Ns-4C-GA and INS groups (Figure f), whereas there was no significant difference between the treated and diabetic groups for AST (Figure e). ALT is a more specific liver enzyme than AST and ALP (both of which are expressed in other organs). , Gamma Glutamyl Transferase (GGT) was also analyzed, as high plasma GGT levels indicate liver damage seen in NAFLD and liver adiposity. , In this study, plasma GGT concentrations in the terminal plasma were significantly lower in groups P2Ns-2C-GA and P2Ns-4C-GA than in the diabetic group (Figure g). Data from liver panels indicate that treatment with INS-laden nanoparticles significantly improves liver function, particularly in ligand-coated nanoparticle groups.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…However, continuous breakthroughs are still required for their poor pharmacokinetics, low bioavailability, strong side effects, and inaccurate distribution. [29,30] A clinical study involving individuals afflicted with Friedreich's ataxia, a type of brain disease, demonstrated that only high-dose resveratrol (5g/day) alleviated symptoms. However, it showed no impact on mitochondrial function and led to the onset of gastrointestinal adverse reactions.…”
Section: Introductionmentioning
confidence: 99%